2002
DOI: 10.21432/t20k64
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Content and Community in Synchronous and Asynchronous Communication: Virtual Communication in a Graduate Seminar

Abstract: A group of graduate students and an instructor at the University of Saskatchewan experimented with the use of synchronous communication (chat) and asynchronous communication (bulletin board) in a theory course in Educational Communications and Technology for an eight-month period. Synchronous communication contributed dramatically to the continuity and convenience of the class, and promoted a strong sense of community. At the same time, it was viewed as less effective than asynchronous communication for dealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…He noted that DM provides an additional channel of communicating about course related as well as technical issues. In their study of synchronous chats in a university setting, Schwier and Balbar (2002) found that students were "passing notes" during the public discussion (p.31). The authors report that the majority of these side conversations were purely social.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He noted that DM provides an additional channel of communicating about course related as well as technical issues. In their study of synchronous chats in a university setting, Schwier and Balbar (2002) found that students were "passing notes" during the public discussion (p.31). The authors report that the majority of these side conversations were purely social.…”
Section: Discussionmentioning
confidence: 99%
“…Since, in any classroom situation, some students will be more active than others, Schwier and Balbar (2002) suggest that instructors may want to "nudge some people to join the conversation or offer their thoughts" (p.30). De Schutter et al (2004), however, assert that inviting individual students to speak should be done in a sensitive manner since students' comfort levels with regards to public speaking might vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that social presence is higher in synchronous chat than in asynchronous discussion. For example, Schwier and Balbar (2002) discuss and compare asynchronous discussion to synchronous chat in a graduate education course. The enrolled students were professionals with families, living quite far from campus.…”
Section: Synchronous Communicationmentioning
confidence: 99%
“…Research indicates that teacher immediacy is more easily afforded through synchronous online interactions (Pelowski, Frissell, Cabral, & Yu, 2005;Schwier & Balbar, 2002) and that increased teacher immediacy is related to increased student outcomes and affect (Arbaugh, 2001;Baker, 2004;McAlister, 2001).…”
Section: Immediacymentioning
confidence: 99%